ORTHOGRAPHIC PERFORMANCE PROFILE OF STUDENTS WITH DYSLEXIA AND LEARNING DIFFICULTIES - Chiaramonte, Thais Contiero [UNESP]; Capelini, Simone Aparecida [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
It is described in the literature that students with specific learning difficulties and disorders may present difficulties in the spelling appropriation of the Brazilian Portuguese writing system, however little is discussed about which errors are most committed by these populations. Thus, this study aimed to characterize and compare the orthographic performance of students with Dyslexia, Learning Disabilities and good academic performance. 75 school children participated, from 9 to 11 years old, divided into 3 groups and matched by diagnosis and school year. Spelling was evaluated by dictating words and pseudowords based on the semiology of errors. The results were compared statistically by the Kruskal-Wallis test adjusted by the Bonferroni Correction, where it was possible to observe that the spelling profile of students with dyslexia and learning difficulties are similar, while the profile of students with good academic performance differs from the other groups, also concluding that the Pseudowords Dictation test is the best to differentiate students with Dyslexia of students with learning difficulties and good academic performance.
Keywords: Dyslexia; Evaluation; Learning; Specific learning disorder; Handwriting